PENGARUH BAURAN RROMOSI, KUALITAS LAYANAN DAN CITRA PERUSAHAAN TERHADAP NIAT MEMBELI KEMBALI PADA PLANET CELLULAR DI KOTA PALU - Yulianto, Agus (Katalogis, 2017)
The purpose of this study are: 1) to determine and analyze the effect of promotion mix on repurchase intention at The Planet Cellular Palu; 2) to determine and analyze the effect of service quality on store image; 3) Â to determine and analyze the effect of service quality on repurchase intention at The Planet Cellyular Palu; 4) determine and analyze the effect of store image on repurchase intention at The Planet Cellular Palu. the sample of this study consist of 220 people who are selected by using accidental sampling technique. The study use Structural Equation Modeling (SEM)Â  to test the hypothesis. The result shows that: 1) promotion mix has positive and significant effect on repurchase intention at The Planet Cellular Palu 2) service quality has positive and significant store image; 3) service quality has positive and significant effect on repurchase intention at The Planet Cellular Palu; 4) storeimage has positive and significant effect on repurchase intention at The Planet Cellular Palu.